Beneath loch ness - Vandiver, Scott E.; Comisky, Chuck ([S.l.] : International Film Group, 2001)
Commissioned by the Adventure Channel, Professor Gus Egan is sent to Scotland to validate his theory that Loch Ness was once a prehistoric breeding ground for ancient marine reptiles. While diving, Egan meets an untimely death when a fault line ruptures deep below the surface of the Loch
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Executive producer, Richard Hughton, Kirk Friedman ; editor, Sheril Schlesinger ; writer, Shane Bitterling, JUstin Stanley, Chuck Comisky
Starring: Patrick Bergin, Lysette Anthony, Lysa Apostle
Keywords: Monsters in motion pictures; Sea in motion pictures; Loch Ness monsters